The Effect Brand Love And Brand Personality On Brand Loyalty: Study On Member Fans Club Football Manchester United In Indonesia - Suhaemi, Muhamad (CV ODIS, 2021)
This study aims to examine the effect of brand love and brand personality on brand loyalty (Study on Members of the Manchester United Football Club Fans in Indonesia). This study used an initial sample of 120 respondents with a purposive sampling technique and the normality test was carried out with 80 outliers. Then performed an analysis of the data obtained in the form of quantitative data analysis and data collection methods in the form of a questionnaire. Quantitative analysis includes validity and reliability tests, classical assumption tests, analysis and multiple regression. The results show that partially conclude that brand love has a significant effect on brand loyalty, brand personality has a significant effect on brand loyalty, and the results show that the influence of brand personality is greater than brand love. The results showed that simultaneously brand love and brand personality have a significance level of 0.000 < 0.05, so simultaneously it states that brand love and brand personality have a significant influence on brand loyalty